City voices : Hong Kong writing in English, 1945 to the present - Xu, Xi, 1954-; Ingham, Michael (Michael Anthony) (Hong Kong University Press, 2003)
City Voices is the first showcase of postwar Hong Kong literature originating in English. Fiction, poetry, essays and memoirs from more than 70 authors are featured to demonstrate 'the rich variety and vitality of the city's literary production'.